Approximate controllability of fractional delay evolution inclusions with noncompact semigroups. (3rd March 2020) - Xiang, Qiao-Min; Zhu, Peng-Xian
ABSTRACT: This paper is devoted to investigate the control systems governed by nonlinear fractional delay evolution inclusions (FDEIs) with noncompact semigroups. Under suitable assumptions, sufficient conditions for approximate controllability of FDEIs are established. The approximate controllability results are further extended to FDEIs with nonlocal conditions, where the compactness or Lipschitz continuity on the nonlocal functions is not required. Finally, two examples are given to illustrate the effectiveness of our conclusions.